The Achievements and Failures of the South Asian Association for Regional Cooperation (SAARC) - Bhattarai, Prakriti (Political Science Journal, 2025)
This study explores both the achievements and failures of the South Asian Association for Regional Cooperation (SAARC) within the socio-political and economic context of South Asia. Established in 1985, SAARC was envisioned as a regional bloc to foster economic collaboration, cultural exchange, and social development among its eight member states—Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka. Despite nearly four decades of existence, SAARC has struggled to become a strong regional organization akin to the Association of Southeast Asian Nations (ASEAN) or the European Union (EU). This research adopts a qualitative methodology, incorporating case studies, expert interviews, and document analysis to provide a nuanced understanding of SAARC’s trajectory. While SAARC has made notable progress in areas such as disaster management, trade agreements, and cultural exchanges, its effectiveness has been constrained by geopolitical tensions—especially between India and Pakistan—economic disparities, and the absence of a robust enforcement mechanism. By drawing comparisons with ASEAN and the EU, this study seeks to analyze SAARC’s challenges and propose recommendations for enhancing its role in regional cooperation.